Mission: Concept in Context : Post-Communism Religious Revival in Eastern Central Europes Experienced in the Seventh-Day Adventist Church - Szabó, László (Book collections on Project MUSE., 2021)
"The modern mission era has experienced in Central and Eastern Europe an unprecedented religious revival in a recent decade. The study with special focus on Hungary elucidates the reasons of overwhelming interest in religious issues and also why Christian churches experienced a loss of confidence and interest in churchgoing within the ten years after the political change in 1989. This case study about Seventh-Day Adventist mission in Hungary underlines that the church needs to recognize the need for reflection and understanding of its own, overall theology and praxis in the light of biblical teachings and of the context of the church's place in society. Otherwise, will mission theology and praxis harvest unsatisfactory results regardless of the invested recourses"--